Subependymal nodules, giant cell astrocytomas and the tuberous sclerosis complex: a population-based study. Issue 9 (2nd May 2008) - O'Callaghan, F J K; Martyn, C N; Renowden, S; Noakes, M; Presdee, D; Osborne, J P
Abstract : Objectives: (1) In a population-based study of tuberous sclerosis (TSC), to identify the number of patients presenting with symptomatic giant cell astrocytomas (GCAs); (2) within a subset of this population, to identify the number who would be diagnosed with GCAs on predetermined radiological criteria. Methods: Patients with TSC in Wessex (a geographical region of England) were identified, and their medical history determined. A subset were invited to have a cranial MRI if they did not have a history of a symptomatic GCA and if they were likely to tolerate cranial imaging without a general anaesthetic. Scans were performed according to a standard protocol on a single scanner and were reported blindly by a neuroradiologist. Results: 179 people were identified with TSC. Ten of these had a history of treatment for a symptomatic GCA. Forty-one of the remainder had a cranial MRI. Thirty-nine of these had subependymal nodules, of whom 24 (59%) had at least one (maximum 11) that showed enhancement with gadolinium. In seven (17%), the lesion was >1 cm, and all of these lesions showed gadolinium enhancement. Conclusions: In this study, the proportion of patients with TSC who had a history of symptomatic GCA was 5.6%. In the subset without such a history, who underwent imaging, the number diagnosed as having a GCA on radiological criteria was much higher (59% gadolinium enhancement and 17% >1 cm in size). Screening for GCAs (performing scans on asymptomatic patients with TSC) would therefore identify large numbers of patients who had not presented with symptoms. This finding leads us to recommend that screening should not be undertaken.